KETERANGAN SAKSI KORBAN DALAM PERSIDANGAN TINDAK PIDANA PENCABULAN TERHADAP ANAK (STUDI KASUS DI PENGADILAN NEGERI DENPASAR) - Estiadi, Ficki Indra; Dharmajaya, Ida Bagus Surya; Parwata, I Gusti Ngurah (Kertha Desa, 2023)
Penelitian ini merupakan penelitian hukum empiris yang menggunakan pendekatan masalah yang bersifat atau bermetode yuridis-empiris yaitu masalah yang diangkat dan dikaitkan dengan peraturan perundang-undangan yang berlaku dengan kenyataan pada sistem peradilan pidana tentang keterangan saksi korban dalam persidangan tindak pidana pencabulan anak. Penelitian menggunakan teknik pengumpulan data melalui teknik wawancara dan pengumpulan data dari bahan- bahan hukum yang sudah ada. Dari hasil penelitan ini dapat disimpulkan bahwa kekuatan keterangan saksi korban dalam persidangan tidak dapat dijadikan alat bukti keterangan saksi yang sah karena dalam meminta keterangan saksi korban tidak disumpah, tetapi dalam praktek keterangan saksi korban dijadikan keterangan yang menguatkan keyakinan hakim dalam membuat keputusan, dan hambatan dalam penggunaan keterangan saksi korban yaitu terdapat pada saksi korban itu sendiri. Kata kunci: Keterangan Saksi, Tindak Pidana, Anak. This research is an empirical legal research that uses a juridical-empirical approach to problems, namely the problems raised and linked to the prevailing laws and regulations with the reality of the criminal justice system regarding the testimony of victims' witnesses in trials of child sexual abuse. From the results of this research it can be concluded that the strength of the testimony of the victim's witness at trial cannot be used as evidence for valid witness testimony because in requesting testimony the victim's witness is not sworn in, but in practice the victim's witness testimony is used as information that strengthens the judge's conviction in making decisions, and obstacles in the use of the victim's witness testimony is found in the victim's witness itself, because in asking for information the victim witness has trauma in exposing the criminal act he has experienced so it must be done in a special way and the victim's witness provides information without mental or physical pressure. In proving a criminal case, a witness who is expected to be able to reveal a criminal act that has occurred by giving testimony in court is not an adult who can be sworn in before giving testimony as one of the requirements so that a witness's testimony has the power of evidence.   Key words: Witness statements, Crime, Children.